Reciprocal crosses as a tool to evaluate the reproductive isolation in a Orchidaceae hybrid zone - Melo e Gouveia, Tiago Manuel Zanfra de; Pinheiro, Fábio (Revista da Biologia, 2018)
Hybrids are individuals formed when reproductive barriers between closely related species aren’t totally established, and individuals from different species cross. Hybridization is remarkably common in some genus within the Orchidaceae family. On Serra dos Órgãos, Rio de Janeiro, two sister species from the genus Epidendrum: E. secundum Jacq e E. xanthinum Lindl occur sympatrically. Individuals with intermediate traces, supposedly hybrids, also occur. In this work, we evaluate the hypothesis of hybridization between these two species and the intensity of their reproductive isolation. It was possible to detect hybridization using experiments of reciprocal pollination. The low reproductive success observed on hybrid individuals plays a major role as a barrier that promotes reproductive isolation strong enough to maintain these two species apart.